Perancangan Sistem Promosi UMKM Pakaian Wanita Hijab Berbasis E-Commerce untuk Meningkatkan Penjualan di Kec. Ranto Baek - Sipayung, Nurul Hidayah; Annas, Firdaus; Nuraisyah, Nuraisyah (Yayasan Lembaga Studi Makwa, 2023)
In this day and age, everything we need can be obtained quickly and easily due to the advancement of technology. For example, if we want to buy a product or package, we have to buy it directly form the seller or the seller concerned. However, with the development of science and technology that is increasingly complex, we no longer need or do not need to be difficult because now there are stores that sell clothes or other goods online, especially with E-commerce, also referred to as online stores. The emergence of e-commerce has changed the way customers interact with products and shop. Customers can access a wide range of products from various sellers around the world with a few clicks, without having to leave home. Customers will feel comfortable with this, and business, especially Micro, Small and Medium Enterprises (MSMEs), will have an excellent opportunity to reach a wider audience. This research uses a qualitative approach with a development method or Research an Development (R&D). The developmant model used is the 4D model. The result of the research that has been done is an e-commerce-bases promotion system design using Opencart. The findings of this study found that Opencart can be a supporting tool that can improve the promotion of MSME products in the Ranto Baek sub-district. MSMEs can enhance their customer interactions and boost product sales and visibility by urilizing Opencart. Furthermore, Opencart can assist MSMEs in gathering data and analyzing consumer behavior, booth of which can be utilized toe improve marketing strategies and product offerings. Thus, it is hoped that this research can help create an e-commerce promotion strategy that is suitable for MSMEs that sell women’s clothing and hijab to increase their sales in this digital erea